FAKTOR – FAKTOR YANG MEMPENGARUHI GREEN PURCHASE INTENTIONS AIR MINERAL AQUA DI JAKARTA - Njo Felix Andriyanto; Rodhiah Rodhiah (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research is to find out whether environmental awareness, green product advertising, environmental knowledge can affect green purchase intention and whether green purchase intention can affect the environmental knowledge of the people in Jakarta. This research uses descriptive research method. Researchers also used the online survey method to collect data from samples in Jakarta. The probability sampling method is used to facilitate sampling from the population in Jakarta. The results of this study found that environmental awareness and green product advertising have a positive effect on green purchase intention but not significant, for environmental knowledge it has a positive and significant effect on green purchase intention, and green purchase intention has a positive and significant effect on environmental knowledge. The limitation of this research is the number of respondents which there are only 202 respondents due to saving research time. This research also only examines environmental awareness, green product advertisement, environmental knowledge, and green purchase intention variables. Researchers hope that this research can help increase sales and find out how much influence Environmental Awareness, Green Product Advertising, and environmental knowledge have on Green Purchase Intention. Key words: Environmental Awarness, Green Product Advertising, Environmental Knowledge, Green Purchase Intention.